Indigenous Ethnicity and Entrepreneurial Success in Africa : Some Evidence from Ethiopia - Mengistae, Taye (World Bank, Washington, DC, 2014)
Researchers have recently been asking why Asian and European minorities in Africa seem to be more successful in business than are people of indigenous ethnicity. The author draws attention to the significant disparity in business ownership and performance that seems to exist among African ethnic groups as well. After analyzing a random selection of small to medium-size manufacturers in Ethiopia, he finds that establishments owned by an indigenous minority ethnic group, the Gurage, typically perform better than those owned by other (major or minority) groups. Other things being equal, Gurage-owned businesses are normally large, partly because they are bigger as start-ups and partly because they grow faster. And yet Gurage business owners are the least educated ethnic group in the sample. Because the size and growth rate of a business also increases with the entrepreneur's education, the performance of other businesses would have been even worse if their owners hadn't been better educated than the Gurage. Indeed, dropping education variables from the size determination equation drastically reduces the estimated advantage of Gurage-run businesses. This suggests that the observed effect of ethnicity could be indicative of intergroup differences in unmeasured ability. More important, it means that whether or not the effect will persist in the long run will depend on the trend in interethnic differences in investment in education.